Tax Avoidance by Public Firms: Unveiling the Overlooked Economic Consequences - GE, Chao; SU, Wunhong; WONG, Wong Ming (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024, 2024)
The existing literature on tax avoidance of listed firms is rich in research results. Moreover, many tax avoidance studies are closely related to research themes. Still, there are large differences in conclusions and a lack of systematic exploration of their findings and the theoretical mechanisms behind them. In particular, the U.S. and China are rich in research on tax avoidance, and many issues of tax avoidance are viewed differently. Therefore, it is necessary to carry out a systematic review to clarify further the theoretical ideas on the influencing factors and economic consequences of tax avoidance. This study conducts a statistical analysis of 172 empirical studies examining the factors influencing corporate tax avoidance and its economic consequences, including 97 studies on influencing factors and 75 on economic outcomes. Given the close interrelation between these factors and economic consequences, this paper systematically reviews the economic consequences of tax avoidance, building on the research of influencing factors. This approach aims to provide readers with a more comprehensive understanding of the determinants and economic implications of tax avoidance under agency theory. Similar topics are categorized and organized, and related studies’ theories and conclusions are summarized to facilitate a systematic understanding of the progress of tax avoidance research. The literature related to this study was obtained by searching for a summary of the recent empirical literature on the factors influencing firm tax avoidance and economic consequences on ScienceDirect, EBSCO, SSRN, Zhiwang, and Baidu Academic. The study is divided into the possible risks arising from tax avoidance, which are discussed mainly from the perspective of tax agency theory, tax risk, accounting information risk, reputation risk, and financial risk. Tax avoidance is an important and complex issue related to the quality development of firms and the coordination of the interests of various parties, such as the government, shareholders, and managers. This study finds that conclusions based on different systems, perspectives, study designs, and samples may not lead to the same conclusions. This study is dedicated to systematizing the literature on tax avoidance, understanding the various research perspectives, and comparing them. This study contributes to a systematic understanding of the content and perspectives of tax avoidance research. In addition, it provides direction for further work on high-quality firm tax avoidance in the future.